Design, Synthesis, and Anticancer Activity of Novel Enmein-Type Diterpenoid Derivatives Targeting the PI3K/Akt/mTOR Signaling Pathway - Jiafeng Wang; Lu Wang; Yingbo Zhang; Siwen Pan; Yu Lin; Jiale Wu; Ming Bu (Molecules, 2024)
The enmein-type diterpenoids are a class of anticancer ent-Kaurane diterpnoids that have received much attention in recent years. Herein, a novel 1,14-epoxy enmein-type diterpenoid 4, was reported in this project for the first time. A series of novel enmein-type diterpenoid derivatives were also synthesized and tested for anticancer activities. Among all the derivatives, compound 7h exhibited the most significant inhibitory effect against A549 cells (IC50 = 2.16 µM), being 11.03-folds better than its parental compound 4. Additionally, 7h exhibited relatively weak anti-proliferative activity (IC50 > 100 µM) against human normal L-02 cells, suggesting that it had excellent anti-proliferative selectivity for cancer cells. Mechanism studies suggested that 7h induced G0/G1 arrest and apoptosis in A549 cells by inhibiting the PI3K/AKT/mTOR pathway. This process was associated with elevated intracellular ROS levels and collapsed MMP. In summary, these data identified 7h as a promising lead compound that warrants further investigation of its anticancer properties.